Allergen composition analysis and allergenicity assessment of Chinese peanut cultivars. (1st April 2016) - Wu, Zhihua; Zhou, Ningling; Xiong, Faqian; Li, Xin; Yang, Anshu; Tong, Ping; Tang, Ronghua; Chen, Hongbing
Highlights: Allergen composition of 53 Chinese peanut varieties was analyzed systemically. The allergenicity of those peanut varieties was assessed. The relation between allergenicity and allergen composition was discussed. Abstract: Peanut ( Arachis hypogaea ) is among the eight major food allergens in the world. Several attempts have been made to decrease or eliminate the allergenicity of peanut. Systemic screening of thousands of peanut cultivars may identify peanut with low allergenicity. In this study, the allergen compositions of 53 Chinese peanut cultivars were characterized, and their allergenicity to sera IgE of Chinese patients and in a mouse model was assessed. Contents of total protein and allergens were quantified by SDS–PAGE and densitometry analysis on gel. Although the contents of allergens broadly varied among cultivars, they were related to one another. The IgE binding capacity of cultivars was tested by ELISA, and their allergenicity was further evaluated in a mouse model by oral sensitization. Results showed that the allergenicity of peanut was affected by allergen composition rather than a single allergen. Peanut cultivars with low allergenicity may contain more Ara h 3/4 (24 kDa), Ara h 2 and less Ara h 3/4 (43, 38, and 36 kDa), Ara h 6. Screening based on allergen composition would facilitate the identification of low-allergenic peanut.